A mathematical model to identify companies’ adaptation variables to cyber-physical production systems - Dal Forno, Ana Julia; Petri, Rafael Fernando; Kipper, Liane Mählmann; Souza, Antônio Augusto Ulson de; Serrano, Rosiane (Revista de Administração da UFSM, 2025)
Purpose: With the fourth industrial revolution, it becomes necessary to identify how companies are adapting to the use of technologies aimed at cyber-physical production systems. Therefore, this article aimed to develop a mathematical model to identify the degree of maturity of cyber-physical production systems. Design/methodology/approach: The methodology draws from theoretical definitions, followed by a survey, in which 61 medium and large companies from the South of Brazil in the textile and clothing sector participated. Afterwards, a mathematical model was developed with logistic regression. Findings: The results showed that the maturity level was classified as intermediate in the validated textile companies, with opportunities for advances in the implementation of real-time monitoring and other technologies of industry 4.0. This result was expected, given the field studies and observations with companies, which reveal that the mathematical model is valid and can be replicated in other organizations. Research limitations/implications: The restriction is that the model was tested in the reality of the Brazilian textile industries. Originality/value: The originality is to propose a model for using cyber-physical systems as a complement to decision-making in production scheduling with ERP that have finite capacity and thus adding an APS algorithm to assist in monitoring production.